Sex differences in lipid and lipoprotein metabolism - Brian T. Palmisano; Lin Zhu; Robert H. Eckel; John M. Stafford (Elsevier, 2018)
Background: Endogenous sex hormones are important for metabolic health in men and women. Before menopause, women are protected from atherosclerotic cardiovascular disease (ASCVD) relative to men. Women have fewer cardiovascular complications of obesity compared to men with obesity. Endogenous estrogens have been proposed as a mechanism that lessens ASCVD risk, as risk of glucose and lipid abnormalities increases when endogenous estrogens decline with menopause. While baseline risk is higher in males than females, endogenously produced androgens are also protective against fatty liver, diabetes and ASCVD, as risk goes up with androgen deprivation and with the decline in androgens with age. Scope of Review: In this review, we discuss evidence of how endogenous sex hormones and hormone treatment approaches impact fatty acid, triglyceride, and cholesterol metabolism to influence metabolic and cardiovascular risk. We also discuss potential reasons for why treatment strategies with estrogens and androgens in older individuals fail to fully recapitulate the effects of endogenous sex hormones. Major Conclusions: The pathways that confer ASCVD protection for women are of potential therapeutic relevance. Despite protection relative to men, ASCVD is still the major cause of mortality in women. Additionally, diabetic women have similar ASCVD risk as diabetic men, suggesting that the presence of diabetes may offset the protective cardiovascular effects of being female through unknown mechanisms. Keywords: Estrogen, Androgens, Sex differences, Cardiovascular disease, Lipid metabolism, Obesity